Beyond supply chains: investigating the economic impact of logistics performance / Mubarik Abdul Mumin and Ibrahim Nandom Yakubu - Abdul Mumin, Mubarik; Yakubu, Ibrahim Nandom (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
This paper investigates the pivotal role of logistics performance in shaping economic growth in selected West African nations. Employing a rigorous fixed effects methodology over the period 2007–2022, the study unveils compelling insights. Logistics performance emerges as a critical driver of economic growth, emphasizing the need for infrastructure investments. Similarly, industrialization and trade openness have significant positive impacts on economic growth, endorsing pro-manufacturing and trade facilitation policies. Surprisingly, inflation exhibits no direct influence on growth, although prudent monetary management remains vital. These findings carry profound policy implications, advocating for holistic strategies to unlock West Africa's economic potential.